Hubungan Kecerdasan Linguistik dengan Penguasaan Kosa Kata Bahasa Arab Siswa Mts Al Amar Legok Tangerang - Romadhon, Ahmad; Churotul Aeni, Chory (STAINI Press, 2023)
The problem in this study was that there were some students who had not been able to understand the questions properly because of their limited Arabic vocabulary, so they could not answer questions in Arabic correctly and correctly. Meanwhile, teachers do not fully understand the characteristics of students' intelligence, so that students who should receive special attention and guidance in mastering Arabic vocabulary receive less attention. This study aims to determine the relationship between Linguistic Intelligence and Arabic Vocabulary Mastery in Grade VII MTs Al Amar Legok Tangerang. The research method used in the preparation of this thesis is a correlation method with the type of field research (field research). The population in this study amounted to 134 students. In this study, researchers used samples taken from the population, namely 60 respondents consisting of 14 students in class VII-1, 15 students in class VII-2, 16 students in class VII-3, and 15 students in class VII-4. to obtain data the researcher used an instrument in the form of a questionnaire statement on variable X (Linguistic Intelligence) and an instrument in the form of a test for variable Y (Arabic Vocabulary Mastery). Researchers carried out the correlation coefficient technique and the significance of the correlation coefficient on both variables. The final stage of this research is testing the research hypothesis, namely that there is a positive and significant relationship between Linguistic Intelligence and Arabic Vocabulary Mastery. The results showed that, from the calculations in testing the hypothesis, the correlation between the teacher's personality competence and the motivation to learn Arabic has a value of r = 0.761 which is positive. And the correlation between the two variables is at a high value, which is between 0.60 and 0.80. Furthermore, the significant test for an error rate of 5% tcount = 8.92 is greater than ttable = 1.67155, so the null hypothesis is rejected and the alternative hypothesis is accepted. In conclusion, the correlation coefficient between linguistic intelligence and Arabic vocabulary mastery is 0.761, which is significant